Development of specialty outlines for collecting job information in the Radio-Radar Systems career field - Cowan, Gordon E.; United States. Air Force. Air Research and Development Command; United States. Wright Air Development Center; Lackland Air Force Base (Tex.) (Lackland Air Force Base, Texas : Personnel Laboratory, Wright Air Development Division, Air Research and Development Command, United States Air Force : 1960., 1960)
This study investigates the feasibility of using an instrument with standard functional work categories to collect occupational information across different specialties of a maintenance career field and at two skill levels. Specialty Outlines were developed for the 5- and 7-skill level for six AFSCs I the Radio-Radar Systems career field and administered to teams of proficient NCO incumbents. The 7-level outlines were administered twice with a five-week interval and the 5-level outlines were administered once. Analysis of variance techniques were applied to estimates of the percentage of time spent on each of 13 standard functional work categories. Each team of specialists was interviewed to discuss the content and format of the outline for their AFSC. Results of the analyses and interviews indicate that Specialty Outlines using standard functional work categories are (1) reliable instruments, (2) adequate for use across different AFSCs of a maintenance career field at both the 5- and 7-level, and (3) differentiate between the work activities of 5- and 7-level airmen.
"August 1960."
Includes bibliographical references.
Personnel Laboratory Contract No.
Mode of access: Internet.
Keywords: Airmen; Job analysis